Heavy-ion RBS characterization of multilayer TiNx-SiO2-Si structures - Aslanoglou, X.; Evangelou, E.; Konofaos, N.; Dimitriades, Ch.; Kossionides, E.; Kaliampakos, G. (HNPS Advances in Nuclear Physics, 2020)
Multilayer structures consisting of TiNx-SiO2-Si layers operating as MOS devices were constructed and tested for their electrical properties. RBS measurements were performed for the characterization of the structure of the devices. The results show a correlation between the structure found by RBS and the electrical performance of the devices.